2016
DOI: 10.3109/07420528.2016.1149486
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and cancer: Synthesis of experimental data and meta-analyses of cancer incidence among some 1,500,000 study individuals in 13 countries

Abstract: Sleep and its impact on physiology and pathophysiology are researched at an accelerating pace and from many different angles. Experiments provide evidence for chronobiologically plausible links between chronodisruption and sleep and circadian rhythm disruption (SCRD), on the one hand, and the development of cancer, on the other. Epidemiological evidence from cancer incidence among some 1 500 000 study individuals in 13 countries regarding associations with sleep duration, napping or "poor sleep" is variable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 126 publications
1
48
0
Order By: Relevance
“…[1215] Moreover, poor, short sleep and daytime naps have been shown to be associated with an increased risk for the development of colorectal cancer in a recent meta-analysis involving about 1.5 million individuals worldwide. [16] Approximately half of colorectal cancer patients report sleep disruption. [17] Similar figures have been described for circadian disruption in this clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…[1215] Moreover, poor, short sleep and daytime naps have been shown to be associated with an increased risk for the development of colorectal cancer in a recent meta-analysis involving about 1.5 million individuals worldwide. [16] Approximately half of colorectal cancer patients report sleep disruption. [17] Similar figures have been described for circadian disruption in this clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our complements to the study by Liu et al follow meta-analyses into sleep and incident cancer [8). Our impression was that methodology outstripped the capacity of 'usual sleep study data' and this appears the case with regard to the work by Liu et al as well.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…In theory, impaired sleep could be a consequence and/or cause of incident cancer [8]. In practice, Cairns et al suggested complex napping-associated effects after examining information over time: Short-term increases in risk associated with daytime napping, the authors concluded, probably reflected pre-clinical disease and did not evince that napping caused -or contributed to -observed cancer cases [10].…”
Section: • the Association Between Nap And All-cause Mortality Shouldmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, a recent meta-analysis based on seven studies estimated a relative risk of breast cancer close to unity (15), and same tendency is seen for hormone-related cancers, including breast cancer and cancer in general in another meta-analysis (16). Also the most recent meta-analysis by Erren et al (17) confirms no association between "poor sleep" and breast cancer risk (17). Finally, no association between sleep duration and breast cancer prognosis has been found among breast cancer survivors (18).…”
mentioning
confidence: 99%